C.06 A nation-wide prospective multi-centre study of external ventricular drainage accuracy, safety and related complications. (June 2019) - Dakson, A; Kameda-Smith, M; Staudt, MD; Lavergne, P; Eagles, M; Elliott, C; Iorio-Morin, C; Makarenko, S; Althagafi, A; Touchette, CJ; Tso, MK; Christie, S
Abstract : Background: Insertion of an external ventricular drain (EVD) is performed to treat elevated intracranial pressure. EVD catheters are associated with complications such as EVD catheter infection (ECI), intracranial hemorrhage (ICH) and suboptimal catheter placement. As part of the Canadian Neurosurgery Research Collaborative, we sought to investigate the national rate of such complications and their risk factors. Methods: Prospective study of 273 patients from eight academic Canadian neurosurgery centres Results: Infection rate was 6% and predicted by smaller incisions and not peri-procedure antibiotics, tunneling distance, type of antiseptic used or catheter flushing ( p >0.05). The mean duration of EVD was 17.7±3.7 in ECI and ventriculitis group which was significantly higher than in patients without ECI (9.4±8.1) ( p =0.045). Although the risk of developing ICH was 9.3%, symptomatic ICH was rare. Pre-procedure pharmacological DVT prophylaxis predicted EVD-related ICH(OR 4.73). The rate of suboptimal catheter location was 31% and predicted by the number of passes ( p =0.02), but not image guidance, level of training or catheter placement in an operating room setting ( p >0.05). Conclusions: This study reports EVD complication rates and their associated risk factors observed within an academic, multicentre Canadian cohort. This information will help to identify strategies to increase the safety of this common neurosurgical procedure.